الحكامة الجامعية في إطار ضمان جودة التعليم العالي - بغدادي, أميرة; بوزيد, نبيل (جامعة الوادي - University of Eloued, 2021)
يسعى البحث الحالي إلى التعرف على نظام ضمان الجودة في الجامعة الجزائرية من حيث كيفية إنشائه، سيرورته وآليات تطبيقه، من أجل تحسين مستوى مخرجات التعليم العالي في ضوء نوعية التكوين وكفاءة الخريجين. ولعل من أهم الإستراتيجيات التي يجب على الجامعة الجزائرية الاعتماد عليها في سعيها لتحقيق التميز والجودة على مستوى التعليم العالي هو الاهتمام ب "نظام الحكامة الجامعية" الذي يعتبر العمود الفقري لنظام ضمان جودة التعليم العالي. لذلك جعلنا الهدف الرئيسي لهذا البحث هو أولا توضيح مفهوم "الحكامة الجامعية" باعتباره مفهوم حديث نسبيا، ثم الوقوف على أهم مبادئ الحكامة ودورها في تحقيق ضمان جودة التعليم العالي. وقد تم الاعتماد على المنهج الوصفي التحليلي من خلال جمع الأدبيات التي تطرقت إلى الموضوع وتحليلها. الكلمات المفتاحية: ضمان جودة؛ تعليم عالي؛ حكامة جامعية. Abstract: The current research seeks to identify the quality assurance system at the Algerian university in terms of how it is created, its process and mechanisms of application, in order to improve the level of higher education outcomes in light of the types of training and graduates competence. Perhaps one of the most important strategies that the Algerian university should rely on, in trying to achieve excellence and quality at the level of higher education, is the “governance system”, which might be considered as the backbone of the higher education quality assurance system. In this regard we set up our main objective in this research to be first, the clarification of the “governance system” concept, in so far as it is a relatively recent concept, and second, to try to work out the main principles of the university governance system, and its role in achieving the quality of higher education. The collection and analysis of the literature in the present research was mainly based on the descriptive analytical approach.
The university governance system in the context of higher education quality assurance
مقال
Keywords: ضمان جودة؛ تعليم عالي؛ حكامة جامعية.; Quality assurance, Higher education, University governance.